2019
DOI: 10.3390/su11041101
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Leadership and Turnover Intention in Startups: Mediating Roles of Employees’ Job Embeddedness, Job Satisfaction and Affective Commitment

Abstract: Entrepreneurial leadership is critical for the sustainable development of start-ups and plays a key role in employees’ turnover intentions. The purpose of this study was to examine the relationship between entrepreneurial leadership and turnover intentions of employees within enterprises established in the last five years. This paper explored this relationship through multiple serial mediators, specifically, employee affective commitment, job embeddedness, and job satisfaction. A quantitative approach was empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 50 publications
2
47
0
6
Order By: Relevance
“…Further, research has shown that team connectivity enables employees to see the diverse influences from other members as opportunities for learning and growth at work, which would promote learning and creativity ultimately [37]. Since these learning opportunities and cognitive diversities are also pivotal to broadening perspectives, realizing the gaps between current and ideal situations, and providing directions for goal setting, we believe that team connectivity could also enhance the indirect effect of job autonomy and self-employment.…”
Section: The Integrative Modelmentioning
confidence: 95%
“…Further, research has shown that team connectivity enables employees to see the diverse influences from other members as opportunities for learning and growth at work, which would promote learning and creativity ultimately [37]. Since these learning opportunities and cognitive diversities are also pivotal to broadening perspectives, realizing the gaps between current and ideal situations, and providing directions for goal setting, we believe that team connectivity could also enhance the indirect effect of job autonomy and self-employment.…”
Section: The Integrative Modelmentioning
confidence: 95%
“…In the past few years, research on entrepreneurial start-ups has focussed on various aspects of leadership all across the globe such as leadership communication in the context of Chinese start-ups (Men et al, 2018), entrepreneurial behaviour in German and American start-ups (Richter et al, 2018), vertical and team leadership in Slovak start-ups (Ljudvigová & Slávik, 2017), transformational and instrumental leadership in Brazilian start-ups (Chammas & da Costa Hernandez, 2019), entrepreneurial leadership and turnover intention in Swiss start-ups (Yang et al, 2019), leadership lessons in Indian start-ups (Joshi & Achutan, 2018; Singh et al, 2018) and many more. This clearly indicates that the academic fraternity recognises the value of leadership in start-ups and is constantly researching in this domain of high importance.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a substantial proportion of the variability in performance and turnover in higher academic institutions remains unexplained (Shahid, 2018). Higher academic institutions are hubs of the career development of young people (Yang et al, 2019). Young faculty is often struggling to get essential organizational support which may help them to improve their performance (Faberman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%